2015
DOI: 10.1016/j.vaccine.2015.07.096
|View full text |Cite
|
Sign up to set email alerts
|

Delayed BCG vaccination results in minimal alterations in T cell immunogenicity of acellular pertussis and tetanus immunizations in HIV-exposed infants

Abstract: Background Bacille Calmette-Guerin (BCG) is effective in preventing disseminated tuberculosis (TB) in children but may also have non-specific benefits, and is thought to improve immunity to unrelated antigens through trained innate immunity. In HIV-infected infants, there is a risk of BCG-associated adverse events. We aimed to explore whether delaying BCG vaccination by 8 weeks, when in utero HIV is excluded, affected T-cell responses to B. pertussis (BP) and tetanus toxoid (TT), in HIV-exposed, uninfected inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…BCG is the most commonly administered vaccine in world history with billions of doses given globally at or soon after birth to protect against disseminated TB during infancy ( 65 ). In addition to its protective effects against TB, for which there is no established correlate of protection, BCG administration may also enhance Ab responses to unrelated pathogens in human newborns and infants ( 20 , 27 , 28 ) and in newborn mice ( 26 ). Protective heterologous effects of certain live-attenuated vaccines including BCG have been demonstrated that reduce morbidity and mortality beyond what can be attributable to prevention of the target disease ( 23 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BCG is the most commonly administered vaccine in world history with billions of doses given globally at or soon after birth to protect against disseminated TB during infancy ( 65 ). In addition to its protective effects against TB, for which there is no established correlate of protection, BCG administration may also enhance Ab responses to unrelated pathogens in human newborns and infants ( 20 , 27 , 28 ) and in newborn mice ( 26 ). Protective heterologous effects of certain live-attenuated vaccines including BCG have been demonstrated that reduce morbidity and mortality beyond what can be attributable to prevention of the target disease ( 23 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is the only routinely administered neonatal vaccine that induces a Th1-polarized immune response ( 20 ). BCG administration may also, in an age-dependent manner, induce beneficial heterologous (“non-specific” or “trained”) immunity against unrelated pathogens and stimuli ( 21 25 ), impact responses to other vaccines ( 20 , 26 28 ), and immune-modulate in the context of allergic diseases as well ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Whole blood samples from BCG-immunized infants produced less IL-13 and IL-17 upon C. albicans stimulation at 4 months postimmunization than samples from unvaccinated controls [ 40 ]. Increased fraction of IL-2-producing, proliferating CD8 + Bordetella pertussis -specific T cells was found in BCG-vaccinated HIV-exposed uninfected South African infants compared with the control group [ 50 ]. This suggests that BCG may also regulate Th17, Th22 or cytotoxic T-lymphocyte subsets.…”
Section: Mechanisms Implicated In Heterologous Bcg-vaccinated Infant mentioning
confidence: 99%
“…88 Concerns about this approach have been raised, however, as in some studies BCG has lowered all-cause mortality. 89 In addition to HIV-infected infants, a recent study by Kagina et al demonstrated that delaying BCG vaccination from birth to 10 weeks of age in HIV-unexposed infants resulted in higher frequencies of BCG-specific, polyfunctional CD4 T cells at 1 y of age. 90 In contrast, Burl and his colleagues found that delaying BCG vaccination from birth to 18 weeks of age led to decreased IFN-g and IL-17 production in the delayed vaccinated group.…”
Section: An Appropriate Time For Bcg Vaccinationmentioning
confidence: 99%